2002
DOI: 10.1073/pnas.082609299
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection in cerebral ischemia by neutralization of 3-aminopropanal

Abstract: Cerebral ischemia stimulates increased activity of polyamine oxidase, a ubiquitous enzyme that catabolizes polyamines to produce 3-aminopropanal. 3-Aminopropanal is a reactive aldehyde that mediates progressive neuronal necrosis and glial apoptosis. Here we report that increased levels of 3-aminopropanal-modified protein levels in humans after aneurysmal subarachnoid hemorrhage correlate with the degree of cerebral injury as measured by admission Hunt͞Hess grade. In vitro screening of clinically approved drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 33 publications
(43 reference statements)
1
86
0
Order By: Relevance
“…1 There are reports that 3-aminopropanal, which automatically produces acrolein, is generated from spermine and is strongly involved in cell damage during ischemia in rats. 26 Accordingly, data obtained thus far strongly suggest that acrolein is mainly produced from spermine and spermidine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 There are reports that 3-aminopropanal, which automatically produces acrolein, is generated from spermine and is strongly involved in cell damage during ischemia in rats. 26 Accordingly, data obtained thus far strongly suggest that acrolein is mainly produced from spermine and spermidine.…”
Section: Discussionmentioning
confidence: 99%
“…1 There are reports that 3-aminopropanal, which automatically produces acrolein, is generated from spermine and is strongly involved in cell damage during ischemia in rats. 26 Accordingly, data obtained thus far strongly suggest that acrolein is mainly produced from spermine and spermidine.There is a report that SSAT and SMO are induced during kidney ischemia-reperfusion injury in rats. 27 However, the activity of SSAT, AcPAO, and SMO at the locus of infarction only slightly increased compared with the activity at the same locus of control mice.…”
mentioning
confidence: 99%
“…12,13 It has been reported that acrolein can also be produced from membrane phospholipids, although the major aldehydes produced during lipid peroxidation are 4-hydroxy-2-nonenal and malondialdehyde. 14 We measured acrolein produced from arachidonic acid under the same conditions in which acrolein has been reported to be produced from membrane phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…Since acrolein is known to be spontaneously generated from 3-substituted propanals [11] and that 3-aminopropanal and H 2 O 2 , the ÅOH radical precursor, are co-generated in spermine enzymatic oxidations by SMO and PAO, the involvement of acrolein and ÅOH radical in the reported cellular deaths in these episodes, appear to be the most likely explanation. A conclusion supported by the observed neutralization of the resulting cytotoxicity with sulfhydryl compounds [89], chemicals that rapid and preferentially reacts with acrolein. Subsequent reports on increases in spermine-oxidase activities and acrolein protein complexes in the blood of patients with strokes [90,91], strongly further support the involvement of acrolein and ÅOH radical in these ischemic events.…”
Section: Published Empirical Datamentioning
confidence: 71%